DAMPAK PELAYANAN TERHADAP LOYALITAS PELANGGAN (Studi kasus pada UD. Cahaya Unggas) - Mursalim Mursalim (Yayasan Akrab Pekanbaru, 2018)
This study aimed to analyze the influence of the service quality, customer loyalty at UD. cahaya unggas in Konawe Southeast Sulawesi. Sampling conducted using purposive sampling technique of 100 respondents. Data were collected by using the questionnaire method is to provide a list of statements and questionnaires directly to the respondents. Data analysis techniques in this study using PLS analysis. Results of this study indicate that the service quality affects toward customer loyalty. Keywords: service quality and customer loyalty.